Revisiting Punjab’s Transformative Journey, 1947-1966: An Appraisal - Bhardwaj, Vikram; Sharma, Usha (European Scientific Journal, ESJ, 2024)
"Punjab, often referred to as the 'Land of five rivers,' has been a significant player in shaping India's historical narrative, leaving an enduring mark on its trajectory. This imprint stems from the courageous and patriotic endeavours of the people of Punjab, who have etched out a distinctive place for themselves. A comprehensive study of its people becomes imperative to comprehend the nuanced dynamics of Punjab's history. This involves delving into their historical, cultural, and religious roots and understanding their political legacy. The year 1947 marked India's liberation from British rule, coinciding with a partition based on the two-nation theory. Punjab bore a heavy toll during this partition, experiencing substantial human and territorial losses. The partition's catastrophic aftermath overshadowed the jubilation of independence for Punjab. Post-partition, Punjab portrayed a sombre and bleak landscape, with the migration of refugees significantly altering the communal composition of the region. This migration upheaved the administrative, economic, and political structures, introducing many complex challenges. The division of Punjab along communal lines generated a palpable sense of indignation and frustration among the Sikh community. The expectations of establishing a Sikh State in independent India, fervently supported by Sikh, Congress, and Hindu leaders, remained unfulfilled. Perceiving an unequal distribution of territory between Hindus and Muslims, the Sikhs advocated for a Punjabi Suba. In their pursuit of this objective, the Akali Dal employed diverse strategies. This culminated in the reorganisation of Punjab on March 21, 1966, leading to its further trifurcation."